THE ASSESSMENT PROCEDURES OF SPEAKING FLUENCY USING RETELLING TECHNIQUE - Hariyanto Hariyanto (Universitas Islam Nahdlatul Ulama Jepara, 2016)
This research is aimed to describe the implementation of speaking fluency assessment using Retelling Technique to the tenth graders of Senior High School students and its procedures. This is based on a study performed by 20 students in the speaking class. Through the implementation of the speaking fluency test and questionnaire given to the students, it can be found that the retelling technique was impractical one to assess fluency since it spent much more time than the conventional technique but was fun to be applied. It is recommended to teacher who wants to apply this method using intensive or interactive kind of speaking to gain more practical, reliable and valid fluency scoring.